Partisipasi Anggota Kelompok Wanita Tani dalam Pelaksanaan Kegiatan Penyuluhan Pertanian di Kota Palembang - Riski, Riski; Oktarina, Selly; Pratiwi, Rizky Amelia (Jurusan Agribisnis, Fakultas Pertanian, Universitas Siliwangi, 2025)
ABSTRACTParticipation is the active involvement of individuals or groups in a process or activity. Women's farmer groups are a forum for the community, especially women, to manage and express various thoughts in the field of agriculture, as well as a means of gaining knowledge together with the group. The implementation of research activities was carried out at the Agricultural Extension Center, the Department of Food Security and Agriculture and Women's Farmer Groups in Palembang City. The objectives of this research activity are 1) To find out the types and forms of participation, 2) To identify factors inhibiting the participation of women's farmer group members and 3) To identify extension techniques used by Agricultural Extension Workers in Palembang City. The data collection method used is primary data from field observations and interviews, while secondary data is data from several sources of studies and reports from related agencies. The results of the study stated that 1) The types of participation of Women's Farmer Group members in Palembang City are in the form of contributions of ideas, energy, and money, while the forms of participation are in the form of meeting attendance, questions and answers, pickets, processing of results, and marketing of harvested results 2) This participation is often hampered by a lack of understanding of how to contribute, minimal training, and difficulty in managing time with other activities 3) Extension techniques carried out by agricultural extension workers in Palembang City are visits, training, individual and group approaches. Keywords: wowen farmer groups, participation, agricultural extension